Monteggia-like lesions: preliminary reports and mid-term results of a single center - Calderazzi, Filippo; Menozzi, Margherita; Nosenzo, Alessandro; Galavotti, Cristina; Solinas, Sofia; Vaienti, Enrico; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the workMonteggia-like lesions are complex and rare elbow injuries. A detailed classification and a proper surgical treatment can provide quite good functional and radiological outcomes. The aim of this retrospective study was to evaluate the mid-term results of Monteggia-like lesions surgical treatment. The other purpose was to investigate whether the complexity of ulna and radius fractures could be prognostic factors of insufficient functional results.MethodsSeven women and five men, with a mean age of 59,25 years who had sustained a Monteggia-like lesion were followed up clinically and radiologically after surgical treatment. The Mayo Elbow Performance Score (MEPS) and the Quick Disabilities of the Arm, Shoulder and Hand (QUICK-DASH) score were used for evaluation at a mean of 17,5 months postoperatively (12-26). The range of movement (ROM), patients’ satisfaction and neurological symptoms were also investigated. Osteolysis, implant loosening and heterotopic ossification were graded. Pearson’s test was used to correlate the different classification systems used (AO/OTA, Bado and Jupiter, PURCCS, Mason) with MEPS and QUICK-DASH score.ResultsThe mean MEPS was 84,92 (65 to 100). The mean QUICK-DASH score was 18,75 (0 to 34,1). The mean active pronation and supination was 72,5° and 59,17°, respectively. The mean active ROM of the elbow was 101,43°. Heterotopic ossifications were absent in six cases but were found in six. No statistically significant correlation was found between the analyzed variables. Conclusions Quite good functional results can be obtained in Monteggia-like lesions if injury pattern is recognized and each component of the injury is addressed. Further studies are needed to determine any prognostic factors.